Optical emission spectroscopy of plasma of underwater electric spark discharges between metal granules - Tmenova, T.A.; Veklich, A.N.; Boretskij, V.F.; Cressault, Y.; Valensi, F.; Lopatko, K.G.; Aftandilyants, Y.G. (Вопросы атомной науки и техники, 2017)
This paper presents series of experiments carried out with granules of Cu, Fe, Mn and Mo. Optical emission spectroscopy techniques were applied for research of the emission spectra of corresponding elements and improvement of the diagnostics of such plasma. Excitation temperature of plasma of underwater spark discharges between copper granules was determined using Boltzmann plot technique. The electron density of the plasma was estimated from broadening of hydrogen Hα line. Представлены серии экспериментов, проведенных с использованием гранул Cu, Fe, Mn и Mo. Спектры излучения соответствующих элементов были получены методами оптической эмиссионной спектроскопии. С их же помощью проводилась диагностика такой плазмы. Используя метод диаграмм Больцмана была получена температура возбуждения электронных уровней плазмы подводного электроискрового разряда между гранулами меди. Уширение линии водорода Hα было использовано для оценки величины электронной концентрации плазмы. Представлені серії експериментів, проведених з використанням гранул Cu, Fe, Mn і Mo. Спектри випромінювання відповідних елементів були отримані методами оптичної емісійної спектроскопії. Із залученням цих же спектрів виконувалась діагностика такої плазми. Температура збудження електронних рівнів плазми підводного електроіскрового розряду між гранулами міді порахована методом діаграм Больцмана. Уширення лінії водню Hα було використане для оцінки величини електронної концентрації плазми.